Higher systemic immune-inflammation index is associated with increased risk of Parkinson’s disease in adults: a nationwide population-based study - Zhao, Jiayu; Wu, Zhipeng; Cai, Fengyin; Yu, Xuejv; Song, Zhenyu (Frontiers in Aging Neuroscience, 2025)
BackgroundThis study aimed to explore the association between a new inflammatory marker, systemic immune-inflammation index (SII), and the risk of Parkinson’s disease (PD) in adult population.MethodsA cross-sectional design was used, participants were recruited from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2020. Three logistic regression models were used to explore the association between SII and the risk of PD, and subgroup analysis and sensitivity analysis were used. In addition, the restricted cubic spline (RCS) was used to explore the dose-response relationship between SII and PD. Receiver operating characteristic (ROC) curves was used to explore the diagnostic value of SII for PD.ResultsA total of 54,027 adults (mean age 35 years) were included in this study. The results of logistic regression showed that after adjusted for all covariates, compared with the Q1 group (lowest quartile in SII), the risk of PD in the Q3 group (OR = 1.82, 95%CI = 1.20–2.82, p < 0.001) and the Q4 group increased (OR = 2.49, 95%CI = 1.69–3.77, p < 0.001), with p-trend < 0.001. After excluding individuals with any missing values, sensitivity analysis also found a positive association between SII and PD. Subgroup analysis showed that this association was more significant in women, younger than 60 years old, non-smokers, alcohol drinkers, non-obese, and without a history of stroke, diabetes, or coronary heart disease. In addition, there was a positive dose-response relationship between SII and PD, and SII had an acceptable diagnostic value for PD (AUC = 0.72).ConclusionSII is positively correlated with the prevalence of PD in the adult population, and SII can help differentiate between PD and non-PD cases.